PENGARUH KOMPETENSI, KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN PEGAWAI PADA DINAS PENDAPATAN DAN PENGELOLA KEUANGAN KABUPATEN BREBES - Dwi Haris Bahtiar; Mr. Tabrani (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2017)
The aims of this research are 1) describe the competition, communication, organization culture, satisfaction, and employee performance; 2) analyze the influence of competition, communication, and organization culture to employee satisfaction; 3) analyze the influence of competition, communication, and organization culture to employee performance; 4) analyze the influence of satisfaction to employee performance; 5) analyze the influence of competition, communication, and organization culture to performance through employee satisfaction. This research develop the research model and four hypothesis to answer the problem of research. Respondent on this research consist of 102 people. The respondent are from all of employees in the revenue office and financial management of Brebes District. This research using Structural Equation Modeling (SEM) which doing through AMOS 190 as the instrument for analysis. Result of the research show that the employee have high competition, high communication, high satisfaction level, high performance level. It can be show from index average of employee performance variable that is in the level 75,98%. Competition, communication, and organization culture significantly influence to employee satisfaction on the revenue office and financial management of Brebes District. Competition, communication, and organization culture significantly influence to employee performance. Employee satisfaction significantly influence to employee performance on the revenue office and financial management of Brebes District. Competition, communication, and organization culture significantly influence to performance through employee satisfaction on the revenue office and financial management of Brebes District. Keywords: competition, communication, organization culture, satisfaction, performance.